Assessment of Weight Loss and Gastrointestinal Symptoms Suggestive of Exocrine Pancreatic Dysfunction After Acute Pancreatitis. Issue 12 (15th December 2020) - Phillips, Anna Evans; Ooka, Kohtaro; Pothoulakis, Ioannis; Paragomi, Pedram; Komara, Nicole; Lahooti, Ali; Harb, Diala; Mays, Melanie; Koutroumpakis, Filippos; Stello, Kimberly; Greer, Phil J.; Whitcomb, David C.; et al.
Abstract : INTRODUCTION: Studies evaluating the natural history of exocrine pancreatic dysfunction (EPD) after acute pancreatitis (AP) are sparse. This study aims to assess incidence and predictors of weight loss and gastrointestinal (GI) symptoms suggestive of EPD 12 months after an AP episode. METHODS: Patients enrolled in the Pancreatitis-associated Risk of Organ Failure Study at the time of an AP episode were included. Weight and GI symptom data were prospectively collected by self-report at enrollment and at 3- and 12-month (windows 2–7 and 8–20) telephone follow-ups. Multivariable logistic regression was used to assess factors associated with ≥10% total body weight loss (EPD surrogate) at 12 months. A generalized estimating equation was used to measure each factor's population effect (in pounds) over 12 months after AP. RESULTS: Follow-up at 12 months in 186 patients (median age = 54 years, 46% men, 45% biliary, 65% first AP attack) revealed weight loss ≥10% from baseline, occurring in 44 patients (24%). Risk of weight loss increased with higher baseline body mass index, previous diagnosis of diabetes mellitus, and worsening AP severity (all P < 0.010). GI symptoms were reported in 13/31 (42%) patients at 12 months. AP severity was independently associated with ≥10% weight loss at 12 months. Over 12 months, men lost more weight than women (average 9.5 lbs); patients with severe AP lost, on average, 14 lbs. DISCUSSION: Weight loss after AP occurs in one-quarter of patients and is associated with AP severity. EPD incidence after AP is likely underappreciated. Further work is needed to assess EPD and potential for pancreatic enzyme supplementation.